A minimum spanning tree stock market analysis of Malaysia technology companies - Zulrushdi, Puteri Nur Qistina Megat; Bahaludin, Hafizah; Ibrahim, Siti Nur Iqmal (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2024)
In this study, the topological structure of Malaysian technology companies stock market was in-vestigated for a one-month period, and a three-month period, before and after the 15th Malaysian General Election. The collected data is the daily closing prices of Malaysia’s top 20 most ac-tive companies based on the volume traded in the list of technology companies. The minimum spanning tree was used to construct the network via Kruskal’s algorithm, and the centrality measures of the stocks, such as degree, betweenness, closeness, and eigenvector, were measured to identify influential stocks. The results show that the connection between stocks in one and three months prior to the election is inconsistent, where variations were exhibited during both periods. Based on centrality measures of degree, betweenness, closeness, and eigenvector, the analysis reveals that over a one-month period, THET, AWAN, GREA, and JHMC consistently rank among the top five most influential stocks before the election, while MMST, MYEG, and GREA dominate as the most influential stocks after the election.